2019
DOI: 10.1080/02713683.2019.1648831
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Müller Glia for Retina Neuroprotection

Abstract: Müller glia constitute the main glial cells of the retina. They are spatially distributed along this tissue, facilitating their close membrane interactions with all retinal neurons. Müller glia are characterized by their active metabolic functions, which are neuroprotective in nature. Although they can become reactive under pathological conditions, leading to their production of inflammatory and neurotoxic factors, their main metabolic functions confer neuroprotection to the retina, resulting in the promotion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 93 publications
(114 reference statements)
1
41
0
1
Order By: Relevance
“…Previous studies indicated that neurotoxic stimuli and glial cell secretion activated the production of not only proin ammatory cytokines but also growth factors in Müller and microglial cells 25,[34][35][36][37] .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies indicated that neurotoxic stimuli and glial cell secretion activated the production of not only proin ammatory cytokines but also growth factors in Müller and microglial cells 25,[34][35][36][37] .…”
Section: Discussionmentioning
confidence: 99%
“…This may explain the fact that retinal damages and visual impairments occurred during the high dose melatonin administration. Müller cells constitute the main glial cells of the retina (Eastlake et al., 2020 ). They are spatially distributed across retinal laminations, facilitating their close membrane interactions with different types of retinal neurons (Di Pierdomenico et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, due to their energy metabolism, Müller cells may protect neurons towards toxic stress by increasing ATP turnover [263]. Furthermore, they play a role in water and ion regulation, buffering the retina and inducing neuroprotection [250,264]. It is worth highlighting the important antioxidant role of Müller cells.…”
Section: Glia-mediated Neuroprotectionmentioning
confidence: 99%